1977
DOI: 10.1002/food.19770210404
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Studies on Egyptian Buffalo Meat Part 3. Determination of Sodium, Potassium and Chloride

Abstract: Sodium, potassium and chloride contents fo buffalo meat were studied in 128 samples. Statistical analysis for the data obtained show significant difference at 0.01 level for sodium, potassium, and chloride in relation to season, and in female in relation to season. Sodium and potassium differs significantly at 0.01 level in male animals in relation to season, and chloride differs at this level due to green season in relation to sex. At 0.05 level sodium shows a significant difference in cut while chloride show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…The present study showed that minerals concentration in meat and liver, without considering the gender and age effect (Table 1), were approximately in line with other reports for buffalo meat (El‐Kirdassy et al. 1977a,b,c; Giuffrida‐Mendoza et al.…”
Section: Resultssupporting
confidence: 93%
“…The present study showed that minerals concentration in meat and liver, without considering the gender and age effect (Table 1), were approximately in line with other reports for buffalo meat (El‐Kirdassy et al. 1977a,b,c; Giuffrida‐Mendoza et al.…”
Section: Resultssupporting
confidence: 93%